Kajian Retrospektif Potensi Interaksi Obat Resep Polifarmasi pada Pasien Poli Jantung di Rumah Sakit X Di Karawang - Ayu Fajariyani; Tyssa Mariyana; Patimah Rachamawati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Drug interactions are part of drug-related problems that can affect patient therapy. These interactions can hinder the achievement of desired therapeutic outcomes. The incidence of drug interactions is increasing as the number of medications received by patients grows. This study aims to identify the presence of polypharmacy prescriptions and their potential drug interactions in cardiology clinic patients at Hospital X in Karawang. The research was observational with a retrospective design, utilizing data from outpatient cardiology clinic prescriptions from January to March 2023 through random sampling. The study results showed that out of 90 prescriptions, 87 (96.66%) had drug interactions, while 3 prescriptions (3.33%) did not. Drug interactions of moderate severity accounted for 239 cases (82.9%), with the most frequent interactions being Furosemide with Bisoprolol, totaling 45 cases (18.8%), and Spironolactone with Bisoprolol, totaling 44 cases (18.4%). Drug interactions of major severity were recorded in 53 cases (17%), with the most frequent being Spironolactone with Ramipril, totaling 20 cases (37.7%), and Spironolactone with Candesartan, totaling 12 cases (22.6%).